Longlegs [videorecording (DVD)] - Perkins, Oz, 1974-; Cage, Nicolas, 1965-; Monroe, Maika; Underwood, Blair; Witt, Alicia, 1975-; Choi-Lee, Michelle; Daulby, Dakota, 1994-; Acala, Lauren; Shipka, Kiernan, 1999- (Decal, 2024)
In pursuit of a serial killer, an FBI agent uncovers a series of occult clues that she must solve to end his terrifying killing spree.